Unbiased screen for pathogens in human paraffin-embedded tissue samples by whole genome sequencing and metagenomics - Nienhold, Ronny; Mensah, Nadine; Frank, Angela; Graber, Anne; Koike, Jacqueline; Schwab, Nathalie; Hernach, Claudia; Zsikla, Veronika; Willi, Niels; Cathomas, Gieri; Hamelin, Baptiste; Graf, Susanne; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Identification of bacterial pathogens in formalin fixed, paraffin embedded (FFPE) tissue samples is limited to targeted and resource-intensive methods such as sequential PCR analyses. To enable unbiased screening for pathogens in FFPE tissue samples, we established a whole genome sequencing (WGS) method that combines shotgun sequencing and metagenomics for taxonomic identification of bacterial pathogens after subtraction of human genomic reads. To validate the assay, we analyzed more than 100 samples of known composition as well as FFPE lung autopsy tissues with and without histological signs of infections. Metagenomics analysis confirmed the pathogenic species that were previously identified by species-specific PCR in 62% of samples, showing that metagenomics is less sensitive than species-specific PCR. On the other hand, metagenomics analysis identified pathogens in samples, which had been tested negative for multiple common microorganisms and showed histological signs of infection. This highlights the ability of this assay to screen for unknown pathogens and detect multi-microbial infections which is not possible by histomorphology and species-specific PCR alone. In summary, the novel metagenomics WGS assay for pathogen detection enables quantitative and unbiased identification of unknown pathogens from FFPE tissue samples, if they are sufficiently abundant. This method is ideal for cases where an infection is suspected based on clinical or histological observations, yet species-specific PCRs are negative.